IMPLEMENTASI MODEL PROBLEM BASED LEARNING DALAM MENULIS TEKS BERITA DI SMP - Helen Manurung; Andiopenta Purba; Yusra D (Universitas Negeri Makassar, 2023)
This study aims to describe the implementation of a problem-based learning model in writing news texts in class VII C SMP Negeri 14 Jambi City. This type of research is descriptive, with a qualitative approach. Data collection techniques are observation, interview, and documentation. The data obtained are the results of interviews with Indonesian language teachers who teach in class VII C related to the learning implementation process. The results of this study indicate that the implementation of the problem-based learning model in writing news texts in class VII C SMP Negeri 14 Jambi City is carried out in accordance with the steps of the problem-based learning model. This can be seen in the steps of problem-based learning, namely orienting students to the problem, organizing students to learn, guiding investigations, developing and presenting work, and analyzing and evaluating the problem-solving process.